PREVALENCE AND RISK FACTORS OF INCISIONAL HERNIA: AN OBSERVATIONAL STUDY - Barabde, Madhuri; Lavankar, Vasant; Deshmukh, Takshak (International Journal of Clinical and Biomedical Research, 2018)
Infection at the surgical site, which leads to the development of excessive tension causing inadequate healing is the most common cause of incisional hernia. Objective: To find out risk factors associated with incisional hernia and its prevalence. Method: A general proforma was prepared for studying each case in detail and underwent routine blood, radiology investigations. A detailed enquiry was made regarding the demographic profile, history of previous operations, its nature and postoperative period. Onset and progress of the hernia were noted. Result: During the study period total operated cases were 921. From that 50 cases of incisional were reported during the follow-up. Out of fifty cases 12 (24%) were male, and 38 (76%) were female. Ratio of male to female is 1:3.2. The difference was found to be significantly significant (p<0.05). Maximum cases were distributed between the age group of 41-50 (32%). Overall highest prevalence of incisional hernia was noted with perforation peritonitis operation, and female it was noted with LSCS operation commonest incision was midline (76 %) which lead to incisional hernia. Conclusion: The prevalence rate of incisional hernia was 5.42%. Overall highest prevalence of incisional hernia was noted with perforation peritonitis operation, and female it was noted with LSCS operation. 76% cases of incisional hernia associated with midline incision.